Random tensor models in the large N limit: uncoloring the colored tensor models - Bonzom, Valentin; Gurǎu, Rǎzvan; Rivasseau, Vincent (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
Tensor models generalize random matrix models in yielding a theory of dynamical triangulations in arbitrary dimensions. Colored tensor models have been shown to admit a 1/N expansion and a continuum limit accessible analytically. In this paper we prove that these results extend to the most general tensor model for a single generic, i.e. nonsymmetric, complex tensor. Colors appear in this setting as a canonical bookkeeping device and not as a fundamental feature. In the large N limit, we exhibit a set of Virasoro constraints satisfied by the free energy and an infinite family of multicritical behaviors with entropy exponents γm=1−1/m.
Gesehen am 05.10.2022